2016
DOI: 10.1186/s12348-016-0078-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of topical ganciclovir in the management of cytomegalovirus (CMV)-related anterior uveitis

Abstract: BackgroundThe aim of this study was to evaluate the efficacy and safety of topical ganciclovir 0.15 % gel in the management of patients with cytomegalovirus (CMV) anterior uveitis.ResultsThis was a retrospective cohort study of the disease course of 31 patients (33 eyes) with aqueous polymerase chain reaction (PCR) positive for CMV. Data from a total of 160 episodes of anterior uveitis flare for 20 years, dating from December 1992 to December 2012, was collected. All patients were treated with concomitant topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 18 publications
1
27
0
4
Order By: Relevance
“…Most studies recommend a 3-month course of oral anti-viral treatment [ 3 , 5 , 6 , 16 ]. Nevertheless, some studies reported that the relapse rate in patients with CMV were high regardless of treatment regimen [ 6 , 17 ]. It was anticipated that antiviral medicines like ganciclovir are virostatic.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies recommend a 3-month course of oral anti-viral treatment [ 3 , 5 , 6 , 16 ]. Nevertheless, some studies reported that the relapse rate in patients with CMV were high regardless of treatment regimen [ 6 , 17 ]. It was anticipated that antiviral medicines like ganciclovir are virostatic.…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings kam es wiederum bei bis zu 75 % der Patienten nach Therapiestopp zu einem Rezidiv [4,5]. Wurde nach initialer topischer Therapie von 5 Applikationen täglich auf eine Langzeittherapie von 3-4 Applikationen täglich umgestellt, konnte eine Reduktion der Rezidive gezeigt werden [6,7].…”
Section: Therapieoptionenunclassified
“…Unsere Ergebnisse decken sich mit den Resultaten anderer Studien. Auch Wong et al fanden eine Reduktion der Schubfrequenz unter topischer Ganciclovir-Therapie in einem mehrheitlich asiatischen Patientenkollektiv unter einer 3-4 × täglichen Applikation [7]. Ebenfalls Antoun et al verwendeten die Therapie langfristig 3-4 × täglich und fanden so eine Abnahme der Schubfrequenz [6].…”
Section: Diskussionunclassified
“… 15 Local ganciclovir therapy has become more popular for producing fewer systemic side effects including intravitreal ganciclovir 16 and topical ganciclovir. Many studies have confirmed the benefits of topical ganciclovir in varying concentrations from 0.15% ganciclovir 17 18 and 0.5% ganciclovir 16 19 to 2% ganciclovir. 20 21 Commercial topical 0.15% ganciclovir gel is available in many countries; however, in some countries such as Thailand, it has not been imported yet.…”
Section: Introductionmentioning
confidence: 95%